Synthesis and Characterization of Molecularly Imprinted Polymer with Oleic Acid as a Template - Siti Maizatul Ameera, Azhar; Muyang, Brody Sambang; Gaanty Pragas, Maniam; Nurlin, Abu Samah (Trans Tech Publications Ltd., 2022)
Molecularly Imprinted Polymer-Oleic Acid (MIPOA) and Molecularly Imprinted Polymer-Palmitic Acid (MIPPA) were synthesized using oleic acid and palmitic acid as the templates; acetonitrile as the porogenic solvent; and allylthiourea as the monomer; and EDGMA as a crosslinker via bulk polymerization. The non-imprinted polymers (NIP) as a control were prepared with the same procedure, but with the absence of template molecule. The synthesized MIPs and NIP were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and the results showed the narrowing of –OH peak which shows that crosslinking has occurred. Field Emission Scanning Electron Microscope-Energy Dispersive X-Ray (FESEM-EDX) was used to analyze the composition of in both MIPs and NIP. The results yielded a composition of C, O, and S. This analysis corresponds to the composition of oleic acid and sulfuric acid as both templates contain -COOH group. These results suggested that the molecularly imprinted polymers can be employed as a potential adsorbent for the removal of oleic acid and palmitic acid from palm fatty acid distillate (PFAD) waste.